Optimasi Sifat Fisik dan Mekanik Sambungan Las TIG (Tungsten Inert Gas) pada Baja SS400 dengan Variasi Nilai Arus Listrik: indonesia - Purwaningrum, Yustiasih; Alvianto, Isal; Sidiq, Reza Arief (UII, 2025)
The study focused on optimizing the physical and mechanical properties of TIG (Tungsten Inert Gas) welded joints on SS400 steel, which is essential to fulfill quality standards in the industry. The aim of this study is to analyze the influence of welding current with variations in values of 85 Amperes, 90 Amperes and 95 Amperes on the physical and mechanical properties of welded joints.The material used was SS400 steel with a thickness of 3 mm. The welding parameters used are AWS A5 12-80 tungsten electrode with a diameter of 2.4 mm, filler ER70S-6 with a diameter of 1.6 mm, argon shielding gas, flow rate 6 liters/minute, voltage 230 V, and welding speed 1.46 mm/s. From the results of the tests carried out, the welding steel that used a current of 95 Ampere has the best performance. The results of the tensile test showed that the tensile strength of this specimen was 390.3 MPa. This value is higher when compared to other current variations which have a value of 224.1 MPa for 85 Ampere and 235.2 MPa for 90 Ampere. In the toughness test, the specimen with a current of 95 Ampere showed the best impact value that reached 1.27 J/mm. Microstructure observation of the specimen showed a phase change where in the HAZ and raw metal regions there were a pearlite and ferrite, then due to the high heat in the welding area and the addition of fillers, the ferrite changed its phase to grain boundary ferrite, Acicular ferrite and Widmanstatten ferrite